Three lessons from the Danish wage compensation scheme - Mikkel Bess; Saman Darougheh (Danmarks Nationalbank, 2021)
This memo aims to take the first steps in analysing the use of the wage compensation scheme in Denmark and its effectiveness to preserve job matches. We find that firms used the furlough programme extensively to save at-risk workers. This focus has been particularly on saving full-time workers and workers with higher tenure.
Keywords: 330; Lohnersatzleistungen; Coronavirus; Dänemark